Golongan Darah dan Transfusi Darah : Bagaimana Prosesnya dan Apa yang Perlu Diperhatikan - Karina Sella; David Valentino; Desi Rahmasari; Pramai Sheila Eka Khoireina; Liss Dyah Dewi Arini (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Blood transfusions are a crucial medical procedure in treating a variety of conditions, ranging from emergency cases such as trauma and heavy bleeding, to chronic diseases such as anemia, thalassemia, and cancer. This procedure not only involves donating blood from the donor to the recipient, but also requires great care at every stage, including the donor selection process, blood type and rhesus examinations, as well as testing for infectious diseases such as HIV, hepatitis B and C, and syphilis. This study aims to examine the blood transfusion process thoroughly and identify critical aspects that must be considered so that the implementation of transfusions runs safely, effectively, and in accordance with national and international medical standards. The method used is a literature study, by collecting and studying various scientific sources, including national and international journals, guidelines from health organizations, and the latest academic literature. The results of the study show that the success of blood transfusions is greatly influenced by a number of important factors, including strict donor screening, efficient blood storage and distribution systems, implementation of appropriate clinical protocols, and education of medical personnel and complete documentation. In addition, it is also important to have a transfusion reaction reporting system as a form of quality control of health services. The implications of this study confirm that blood transfusions are not only a clinical action, but also a complex system and require the synergy of various parties, including health workers, health care institutions, and the community. Therefore, improving the quality of services, strengthening the transfusion information system, and public education campaigns on the importance of voluntary blood donation are strategic steps in supporting safe, sustainable, high-quality, and scientifically evidence-based transfusion practices.